Fatigue perception in a cohort of children with chronic immune thrombocytopenia and their caregivers using the PedsQL MFS: Real‐life multicenter experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP). Issue 3 (4th December 2020) - Lassandro, Giuseppe; Palmieri, Viviana Valeria; Barone, Angelica; Farruggia, Piero; Giona, Fiorina; Licciardello, Maria; Marinoni, Maddalena; Marzollo, Antonio; Notarangelo, Lucia Dora; Palumbo, Giuseppe; Ramenghi, Ugo; Russo, Giovanna; et al.
Abstract: Background: Fatigue is an important clinical and psychological aspect for a significant number of children affected by immune thrombocytopenia (ITP). To date, few studies have explored fatigue and its relationship with chronic ITP in pediatric age. The aim of the present multicentric pilot study is to determine fatigue perception in a large group of children with chronic ITP and their caregivers using the PedsQL Multidimensional Fatigue Scale (PedsQL MFS), and to compare the results with those of healthy control subjects. Procedure: Children with chronic ITP aged 5‐18 years and/or caregivers of children aged 2‐18 years were enrolled. Child/adolescent self‐report was used for patients aged 5‐18 years, and parent proxy‐report for patients aged 2‐18 years. The questionnaire was offered as online survey. PedsQL MFS is composed of 18 items covering three dimensions: General Fatigue Scale, Sleep/Rest Fatigue Scale, and Cognitive Fatigue Scale. Results: One hundred ninety‐one patients affected by chronic ITP and 248 caregivers answered the PedsQL MFS. We have highlighted that lower values of PedsQL MFS scores are obtained in the 13‐18 age group. Moreover, sleep/rest fatigue domain appears to be more compromised in all age groups. For all PedsQL MFS scores, pediatric patients with chronic ITP and their caregivers reported statistically significant worse fatigue than healthy children. Conclusions: This study suggests that fatigue is relevant among children and adolescents affected by chronic ITP. The PedsQL MFS represents an adequate instrument for measuring fatigue in patients with chronic ITP. Therefore, symptoms of fatigue should be routinely assessed in clinical practice.